2015
DOI: 10.1039/c4em00621f
|View full text |Cite
|
Sign up to set email alerts
|

Levels of bisphenol-A in different paper products in Guangzhou, China, and assessment of human exposure via dermal contact

Abstract: Bisphenol A (BPA) is a chemical widely used both in plastics production as a food and beverage container and in thermal papers as a color developer. Dietary consumption is the main route of human exposure to BPA, but dermal absorption through handling different papers might be underestimated or ignored. In this study, BPA in different paper products, including different types of papers, receipts and Chinese currencies, were investigated. BPA was detected in receipts (n = 87) and Chinese currencies (n = 46) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Occurrence of Cl x BPA derivatives has been widely reported in a suite of water bodies bodies (Ballesteros et al, 2006; Bastos et al, 2008; Bourgin et al, 2013a; Bourgin et al, 2013b; Bulloch et al, 2015; Casatta et al, 2015; Chang et al, 2014; Chang et al, 2012; Dorival-Garcia et al, 2012a; Dorival-Garcia et al, 2012b; Dupuis et al, 2012; Fan et al, 2013; Fukazawa et al, 2001; Fukazawa et al, 2002; Gallard et al, 2004; Gallart-Ayala et al, 2007; Gallart-Ayala et al, 2010; Kosaka et al, 2012; Lane et al, 2015; Li et al, 2015; Ruan et al, 2015; Song et al, 2014b; Voordeckers et al, 2002; Yamamoto and Yasuhara, 2002; Yang et al, 2014a; Yang et al, 2014b; Yuan et al, 2011; Yuan et al, 2010; Zafra-Gómez et al, 2008; Zafra et al, 2003). In addition, BPA is frequently detected in thermal receipts (Fan et al, 2015; Hormann et al, 2014) and certain personal care- and household-cleaning products, such as, bar soaps, facial/body lotions, shampoo, dishwashing and laundry detergent, and toilet bowl cleaner (Dodson et al, 2012). Reported BPA levels in these consumer products ranged between <10 μg g −1 and up to ~100 μg g −1 (Dodson et al, 2012), while it was as high as 20 mg g −1 on thermal receipt paper (Hormann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of Cl x BPA derivatives has been widely reported in a suite of water bodies bodies (Ballesteros et al, 2006; Bastos et al, 2008; Bourgin et al, 2013a; Bourgin et al, 2013b; Bulloch et al, 2015; Casatta et al, 2015; Chang et al, 2014; Chang et al, 2012; Dorival-Garcia et al, 2012a; Dorival-Garcia et al, 2012b; Dupuis et al, 2012; Fan et al, 2013; Fukazawa et al, 2001; Fukazawa et al, 2002; Gallard et al, 2004; Gallart-Ayala et al, 2007; Gallart-Ayala et al, 2010; Kosaka et al, 2012; Lane et al, 2015; Li et al, 2015; Ruan et al, 2015; Song et al, 2014b; Voordeckers et al, 2002; Yamamoto and Yasuhara, 2002; Yang et al, 2014a; Yang et al, 2014b; Yuan et al, 2011; Yuan et al, 2010; Zafra-Gómez et al, 2008; Zafra et al, 2003). In addition, BPA is frequently detected in thermal receipts (Fan et al, 2015; Hormann et al, 2014) and certain personal care- and household-cleaning products, such as, bar soaps, facial/body lotions, shampoo, dishwashing and laundry detergent, and toilet bowl cleaner (Dodson et al, 2012). Reported BPA levels in these consumer products ranged between <10 μg g −1 and up to ~100 μg g −1 (Dodson et al, 2012), while it was as high as 20 mg g −1 on thermal receipt paper (Hormann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…, with the most skin absorption through daily contact with different paper products (Bunone, Briand, Miksicek, & Picard, 1996;Demierre, Peter, Oberli, & Bourqui-Pittet, 2012;Fan et al, 2015;Liao & Kannan, 2011;Mielke, Partosch, & Gundert-Remy, 2011). This is particularly true for cashiers who are exposed to thermal paper products every day (Sarigiannis et al, 2016).…”
Section: Ballesterosmentioning
confidence: 99%
“…Although ingestion exposure is the major concern and focus of most BPA research efforts, the dermal exposure of BPA has raised lots of concern and discussion. BPA can be absorbed through the skin effectively (Björnsdotter, de Boer, & Ballesteros‐Gomez, ), with the most skin absorption through daily contact with different paper products (Bunone, Briand, Miksicek, & Picard, ; Demierre, Peter, Oberli, & Bourqui‐Pittet, ; Fan et al, ; Liao & Kannan, ; Mielke, Partosch, & Gundert‐Remy, ). This is particularly true for cashiers who are exposed to thermal paper products every day (Sarigiannis et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bisphenol A (BPA) is a key component to produce various consumer products such as household electronics, medical and dental equipment, beverage cans, kitchen appliances, water and food containers and paper products [1][2][3]. It has now been confirmed that the occurrence of a variety of chronic diseases including female infertility is closely related to BPA exposure [4].…”
Section: Introductionmentioning
confidence: 99%